Computational Red Teaming for Physical Security Assessment - Tan, Terence Peng Lian; Porter, Stuart; Tan, Tele; West, Geoff (Institute of Electrical and Electronics Engineers ( IEEE ), 2014)
Computational Red Teaming (CRT) is a computational approach to test defences. In this paper, we use develop a CRT system to assess the physical security of any building, provided the building is designed with Building Information Models (BIM). BIMs are similar to 3D Computer Aided Design (CAD) models but with the addition of extra layers of information on the building system and components. Through a demonstration attack on a facility, this paper shows how a CRT approach to physical security assessment leads to a deeper and wider analysis of the building. The Red Team attacks every room under varying capabilities. The Blue Team analyses the attack data and strengthens the defences against further attack. Each attack-defend cycle yields a rich set of data that can be analysed by the user. We show that our algorithm performs at O(KLn(m+nlogn) time. We present the effectiveness of our system based on recent developments in physical security assessment.